New records of Harpacticoids (Crustacea, Copepoda) from a coastal system of northern Colombia - Fuentes-Reinés, Juan M. (2022)
Three species of harpacticoids are herein recorded from the zooplankton of Rodadero beach, Santa Marta, Magdalena, Colombia. Samples were collected from the littoral zone, mainly at inshore areas covered by mangrove vegetation and in an adjacent oyster bank. One of them, Laophonte cornuta Philippi, 1840 is new to the Colombian harpacticoid fauna, the other two species: Distioculus minor (Scott T., 1894) and Microsetella norvegica (Boeck, 1865) are new reports to the Magdalena department. This is the first illustrated record confirming their presence in Colombia and Magdalena, northern Colombia. Comparative morphological comments and illustrations of these species are also provided to document this report.